Migrant Workers in Patriarchal Power A Study of Family Power in Gondanglegi - Dewi Amelia (Lembaga Penellitian, Pengabdian dan Publikasi (LP3M), UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2024)
The phenomenon of labor migration, particularly female migrant workers, has become an increasingly relevant issue in the context of globalization and economic dynamics. This study aims to explore the experiences of Indonesian female migrant workers in facing the patriarchal power structures within their families and the socio-economic impacts resulting from their decision to work abroad. Using a qualitative approach with phenomenological methods, the research examines the stories of four female migrant workers ; Mrs Fadilah, who works in Taiwan due to the family’s economic limitations ; Mrs Ngatipah, who has worked in Hong Kong for 25 years due to an irresponsible husband ; Mrs. Suadah, who had to migrate because her husband was indifferent to living expenses ; and Mrs Mudrikah, who works in Saudi Arabian after divorcing her husband. The Findings show that although these women face significant challenges in family relationships and social norms, they remain agents of change, bringing positive impact to the family power structure. Gender role change occur due to the tension between traditional roles and their new role as primary breadwinner. Desite cultural and social obstacles, female migrant workers can bring about transformations in gender relations, potentially creating more equitable families. This study emphasizes the importance of gender-sensitive public policies to support female migrant workers and raise public awareness of their contributions to the economy and social change.